(untitled) (Indian Journal of Arid Horticulture, 2025)
The study aimed to standardize the most suitable propagation method (budding and grafting) and optimal timing to achieve maximum success rates in bael under the semi-arid conditions of Uttar Pradesh, India. The findings revealed that the minimum number of days to bud sprouting (15.71 days) was observed with softwood grafting conducted on 15th April. This method and timing also resulted in the highest sprouting success rate (83.33%) and the greatest bud and graft success rate (56.67%). Furthermore, the highest survival percentage of grafted plants was recorded with softwood grafting on the same date. From this study, softwood grafting during the month of April is recommended for the successful propagation of bael in semi-arid regions of Uttar Pradesh.